Novel indexes for diagnosing metabolic syndrome in apparently healthy Gujarati Asian Indians: a cross-sectional study. Issue 11 (15th April 2016) - Joshi, Hasit; Shah, Komal; Patel, Priyanka; Prajapati, Jayesh; Parmar, Meena; Doshi, Dhaval; Chaurushia, Shardul
Abstract : Background: We aimed to compare the diagnostic accuracy of four novel indexes—triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio, weight height ratio (WHtR), lipid accumulation product (LAP) and visceral adiposity index (VAI) with conventional components of metabolic syndrome (MetS) in order to identify a single index for the diagnosis of MetS in Gujarati Indian population. Methods: This observational and cross sectional study involved a total of 3329 healthy adults of 18–79 years of age. Demographic and clinical data such as body mass index, waist circumference, blood pressure were measured along with the levels of lipids and fasting blood glucose. Results: The overall prevalence of MetS was 34.32%, which was almost double in older individuals (45.5% vs. 20.8%) and slightly higher in males (37% vs. 31.2%). In comparison to individual components of MetS, three novel indexes—VAI, LAP and TG/HDL-C ratio showed superior diagnostic efficacy yielding an area under curve of 0.856, 0.821 and 0.821 respectively. The optimal cut-offs for VAI, LAP and TG/HDL Ratios for male, females, young and old population are (79.71, 88.12, 75.42, 87.4), (35.62, 34.73, 35.88, 34.7) and (2.249, 3.16, 2.49, 2.79) respectively. The diagnostic effectiveness of novel markers was unaffected by the age and gender of an individual. However, the efficacy of WHtR was comparable with the other conventional markers. Conclusion: Three novel markers—LAP, VAI and TG/HDL-C ratio could be effectively used as a single 'Surrogate marker' for screening of asymptomatic Gujarati Asian Indians with MetS.